Употребата, значењето и изработката на Мијачките семејни знамиња - The Use, Meaning and Making of the Mijak Family Flags - Damjan Buzharovski (Македонски хералд - Macedonian Herald, 2022)
Every Mijak family in the past had its own flag. The use of the family flags is associated with several customs, which were performed during their display, carrying, and finally disposing. Without performing those customs and rituals, the flag would not have been hoisted. These flags had their own symbolism and meaning for which they were used. The wedding in the Mijak villages did not start, without displaying the flag in the house where the wedding took place. If the flag was not displayed, it meant that some accident had happened, or if it was disposed immediately after the wedding, it meant that the bride was dishonest.